31.9k views
3 votes
(2^2b^-2)^-3
Math help plz

User Shavana
by
6.0k points

1 Answer

4 votes

Answer:


(b^6)/(64)

Explanation:

We need three rules. Raising a power to a power. Raising a product to a power. Raising a number to a negative exponent.

Rule 1:

To raise a power to a power, multiply powers.


(a^m)^n = a^(mn)

Rule 2:

To raise a product to a power, raise every factor of the product to the power.


(a^xb^yc^z)^n = a^(xn)b^(yn)c^(zn)

Rule 3:

To raise a number to a negative power, follow this formula.


a^(-n) = (1)/(a^n)

Your problem.


(2^2b^(-2))^(-3) =

You have a product raised to a power, so raise each factor to the power.


= (2^2)^(-3)(b^(-2))^(-3)

Now raise each power to a power by multiplying exponents.


= 2^(2 * (-3))b^(-2 * (-3))


= 2^(-6)b^(6)

Now we follow the rule of a negative exponent.


= (1)/(2^6) * b^6


= (b^6)/(2^6)


= (b^6)/(2 * 2 * 2 * 2 * 2 * 2)


= (b^6)/(64)

Answer:
(b^6)/(64)

User Dat TT
by
5.4k points